Odločitveni model povezovanja računovodske in tehnične evidence gospodarske javne infrastrukture - Pergar, Petra (Geodetski vestnik, 2013)
One of the key issues in the planning, construction and management of public service infrastructure is financing such infrastructure and ensuring its longterm reliability. For this purpose, it is necessary to establish effectiveasset management tools. The basis for the creation of such tools is relevant registers. In Slovenia, the technical register and fixed assets register of public service infrastructure both represent the same subject fromdifferent points of view, but they are usually not interconnected. Qualitative and quantitative analyses of both registers in 13 local communities in Slovenia were used to develop a decision model for the integration of the fixed assets register and the technical register of public service infrastructure. The proposed decision model will offer local communities one possible approach for connecting the technical register and fixed assets register of public service infrastructure. This will be the firststep towards the establishment of effective asset management tools for managing public service infrastructure.
Keywords: evidenca osnovnih sredstev; fixed assets register; gospodarska javna infrastruktura; public service infrastructure; technical register; tehnična evidenca gospodarske javne infrastrukture